Agroforestry in Shade Coffee Plantations as an Emission Reduction Strategy for Tropical Regions: Public Acceptance and the Role of Tree Banking - Nandakishor, T. M.; Gopi, Girigan; Champatan, Vipin; Sukesh, A.; Aravind, P. V. (Frontiers in Energy Research, 2022)
Support for the adoption of climate change mitigation measures in low-income regions depends on how such activities contribute to generating household income and gaining confidence from the local community. The planning of mitigation measures or pro-environmental activities needs to consider the cost of deployment, customization of activities according to local conditions and socio-cultural background and perceptions of people. This paper analyses the incentive induced ‘agroforestry’ or ‘planting trees in farmland’ as part of the Carbon Neutral Programme supported by the Government of Kerala in Meenangadi Grama Panchayath, Wayanad district. An increase in tree cover is proposed as a strategy for increasing carbon sequestration. Planting more trees in farmland (except grain cultivated areas) along with crops, according to farmers, may reduce crop yield and discourage farmers’ participation. The Government of Kerala put forward the concept of a tree banking/ tree incentive program to attract farmers to expand tree cover. A survey was conducted to assess the perceptions and concerns of farmers about the proposed ‘Agroforestry ‘/Tree Banking program. Tree Banking Programme designed to encourage farmers to plant trees has gained public interest, and the study also documented the factors influencing the willingness of farmers for planting trees. The study revealed that the majority of the individuals (93% of the survey participants) residing in the region are interested in supporting the activities for climate change mitigation. Financial incentives announced under tree banking generated interest among farmers. 89% of the survey participants consider the incentive scheme to be an attractive option, as it can compensate for the short-term loss in crop productivity. However, farmers were very selective in choosing the tree species to be planted in their farms. Incentivization helps to make sure that a large proportion of the planted saplings will grow into mature trees. Overall, it can be concluded that afforestation in the form of agroforestry could be potentially attractive to the farmers and contribute towards achieving carbon neutrality for tropical agricultural areas.